Home / ECE / Signals and Systems :: Discussion

Discussion :: Signals and Systems

  1. If Laplace transform of f(t) is F(s), then =

  2. A.
    s F(s) - f(0-)
    B.
    C.
    s F(s) + f(0-)
    D.

    View Answer

    Workspace

    Answer : Option A

    Explanation :

    £f(t) =

    £-1F(s) = f(t)

    £[a f1(t) + bf2(t)] = aF1(s) + bF2(s)

    where

    £[f(t - T)] = e-sT F(s)

    £[e-at f(t)] = F(s + a)

    Initial value theorem

    Final value theroem

    Convolution Integral

    where t is dummy variable for t.


Be The First To Comment